Factors influencing success rate of intracytoplasmic sperm injection with azoospermic male patients = Faktoren, die die Erfolgsrate der intrazytoplasmatischenSpermieninjektion bei Männern mit Azoospermie beeinflussen - Rehnitz, Julia; Rösner, Sabine; Harsch, Juliane; Dietrich, Jens Erik; Bruckner, Thomas; Capp, Edison; Strowitzki, Thomas; Germeyer, Ariane (Geburtshilfe und Frauenheilkunde, 2020)
Azoospermia affects about 1% of men, of whom up to 15% inquire about infertility treatment. Information about predictive factors for these couples is very limited. Patients, Materials and Methods We performed a retrospective analysis of the clinical records of 118 cycles of intracytoplasmic sperm injection treatment after testicular sperm extraction for male azoospermia carried out between January 2008 and October 2015. Of those, 66 were first, 35 second, and 17 third cycles. Statistical significance was set at p < 0.05. Predictive factors for successful pregnancy were evaluated and included male/female age, male/female body mass index, male/female nicotine use, and histological results of testes biopsies. Results Embryo quality and the number of embryos transferred were positively associated with pregnancy success (p = 0.003). Males whose partners conceived had a significantly lower body mass index than those whose partners did not conceive (p = 0.023). Neither female weight nor age nor smoking status of the male or female were significant factors. In cases with tubular atrophy ≥ SIGG grade 4 the chance of pregnancy was poor, irrespective of the existence of mature sperm and the number of cycles performed. Conclusion Overweight male patients should be advised about weight reduction prior to treatment, and counseling about success rates should include histological and sperm-positive biopsy results.
Gesehen am 12.10.2020